The cartographic perspective of the sports geography. Football players in the pre- and post-war Polish football league - Nieścioruk, Kamil (Studia Geohistorica, 2022)
Football, like any sport and most phenomena, has its spatial dimension. And due to its popularity, it also reflects social and demographic changes. The paper presents qualitative and quantitative characteristics of selected football clubs, with a focus on the spatial-demographic features of players. Three pre-war seasons and one of the first post-war seasons have been analysed. The result is the proposition of a methodological approach to visualise multi-attribute sports data and an insight into the influence of migration, geopolitics, border changes and history on Polish football.